Policy Making and Citizen Participation in Zimbabwe: the Case of ZIMASSET - Mazundu, Fact D. (Midlands State University, 2017)
The issue of citizen participation in policy formulation in Zimbabwe has been a bone of contention since independence. High sounding policies and blueprints have been implemented since 1980 but have not been beneficial to majority of the citizens of Zimbabwe. ZIMASSET is one of these policies that have lacked citizen participation as revealed by the findings of this research. Predecessor policies of ZIMASSET such as ESAP, ZIMPREST and MERP have faced the same fate of ignoring the views of the general citizens and were unsuccessful in addressing the actual needs to the citizen’s welfare needs. This research aimed to unravel whether the citizenry was engaged in the policy making processes of the ZIMASSET policy. This research was conducted using a descriptive method which encompasses both quantitative and qualitative methods of research. Questionnaires were distributed and interviews were conducted in the provinces of Bulawayo and some districts of Midlands province. The research unraveled that ZIMASSET policy was implemented without the consultation of the general citizens public forums and consultative meetings were not organized by the government or public authorities in a bid to find out the real problems faced by the citizens and how they think the problems can be solved. Majority of the respondents got to know about this policy through the media rather than through the policy makers themselves.